DISIPLIN WARGA BELAJAR DALAM MENGIKUTI PENDIDIKAN KESETARAAN DI PKBM INSAN CENDEKIA KOTA PEKANBARU - Wina Monica Sari; Aswandi Bahar; Widiastuti Widiastuti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to determine the high level of learning wisdom in following the program in PKBM Insan Cendekia in Pekanbaru City. The formulation of the problem in this research is how high the level of learning of citizens in education lessons in PKBM Insan Cendekia Pekanbaru City. After this research is conducted, it is expected to improve the discipline of citizens learning PKBM Insan Cendekia from the discipline of learning citizens in education at PKBM Insan Cendekia Pekanbaru City. This research uses descriptive research type with quantitative approach. Sampling technique in this research use saturated sampling that is sample determination technique used as sample (Sugiyono, 2015: 124). Technique of taking data in this research is by using questionnaire as method data, which discuss 114 item statement. After a questionnaire was proven, 9 items were invalid. Data were obtained from respondents who lied 20 people for questionnaire trials. So to research item 105 statement propagated to 43 respondents. The results of data analysis show that the discipline of learning in the education of PKBM Insan Cendekia Pekanbaru City of authoritarian discipline classified in very high interpretation dengon average score of 83.28% average. PKBM Insan Cendekia's parties are more akin to authoritarian authority. Citizens who use the existing rules because there will be punishment or punishment obtained due to regulations. Keywords: Discipline, Citizen Learning, Equality Education